The Risk of Fatigue and Sleepiness in the Ridesharing Industry: An American Academy of Sleep Medicine Position Statement - Berneking, Michael (J Clin Sleep Med, 2018)
The ridesharing—or ride-hailing—industry has grown exponentially in recent years, transforming quickly into a fee-for-service, unregulated taxi industry. While riders are experiencing the benefits of convenience and affordability, two key regulatory and safety issues deserve consideration. First, individuals who work as drivers in the ridesharing industry are often employed in a primary job, and they work as drivers during their “off” time. Such a schedule may lead to driving after extended periods of wakefulness or during nights, both of which are factors that increase the risk of drowsy driving accidents. Second, these drivers are often employed as “independent contractors,” and therefore they are not screened for medical problems that can reduce alertness, such as obstructive sleep apnea. Some ridesharing companies now require a rest period after an extended driving shift. This measure is encouraging, but it is insufficient to impact driving safety appreciably, particularly since many of these drivers are already working extended hours and tend to drive at non-traditional times when sleepiness may peak. Therefore, it is the position of the American Academy of Sleep Medicine (AASM) that fatigue and sleepiness are inherent safety risks in the ridesharing industry. The AASM calls on ridesharing companies, government officials, medical professionals, and law enforcement officers to work together to address this public safety risk. A collaborative effort is necessary to understand and track the scope of the problem, provide relevant education, and mitigate the risk through thoughtful regulation and effective fatigue risk management systems. CITATION: Berneking M, Rosen IM, Kirsch DB, Chervin RD, Carden KA, Ramar K, Aurora RN, Kristo DA, Malhotra RK, Martin JL, Olson EJ, Rosen CL, Rowley JA, Gurubhagavatula I, American Academy of Sleep Medicine Board of Directors. The risk of fatigue and sleepiness in the ridesharing industry: an American Academy of Sleep Medicine position statement. J Clin Sleep Med. 2018;14(4):683–685.